2015
DOI: 10.1016/j.mjafi.2013.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of high altitude pulmonary edema in low-landers during re-exposure to high altitude after a sojourn in the plains

Abstract: Incidence Pulmonary edema of mountaineers a b s t r a c tBackground: There is uncertainty whether acclimatized low-landers who return to high altitude after a sojourn at low altitude have a higher incidence of pulmonary edema than during the first exposure to high altitude. Methods: This was a prospective cohort study consisting of men ascending to 3400 m by road (N ¼ 1003) or by air (N ¼ 4178). The study compared the incidence of high altitude pulmonary edema during first exposure vs the incidence during re-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Moreover, HAPE is a rare disease with a reported incidence of 0.31 % in Northern Himalayas and incidences of HA related illnesses are known to reduce with acclimatization [12].This has been acknowledged by the authors as well. In a disease with such a low incidence, practical use of measurement of inflammatory markers for identification of individuals at risk of HAPE remains to be seen considering the extensive interaction between hypoxia-related and inflammatory chemical pathways [13] and wide arrays of inflammatory, infectious and other conditions which are likely to cause elevation of chemokines in participants [6].…”
Section: To the Editormentioning
confidence: 84%
“…Moreover, HAPE is a rare disease with a reported incidence of 0.31 % in Northern Himalayas and incidences of HA related illnesses are known to reduce with acclimatization [12].This has been acknowledged by the authors as well. In a disease with such a low incidence, practical use of measurement of inflammatory markers for identification of individuals at risk of HAPE remains to be seen considering the extensive interaction between hypoxia-related and inflammatory chemical pathways [13] and wide arrays of inflammatory, infectious and other conditions which are likely to cause elevation of chemokines in participants [6].…”
Section: To the Editormentioning
confidence: 84%
“…We are pleased to receive such an early response to our paper comparing the incidence of high altitude pulmonary edema (HAPE) after the first exposure and after re-exposure to high altitude. 1 The letter gives us an opportunity to delve deeper and educate ourselves about finer points (for us) in epidemiology. It also commends our efforts in conducting this longitudinal study, and we express our thanks for this.…”
Section: Replymentioning
confidence: 99%
“…It appears like a black colored, thread-like eruption, closely mimicking cutaneous larva migrans. 1 It is a rare condition and since 1957 only 26 cases have been reported. 1,2 Most of the cases of CPM are reported from Asia; however, it has been rarely reported from India; one of the authors has reported a pediatric case of CPM.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HAPE is a rare disease, as acknowledged by the authors, and has an incidence of only 0.31% among Indian male lowlanders after an acute ascent (by air) to an altitude of 3,400 m in the Western Himalayas. 5 …”
mentioning
confidence: 99%